GABAergic signaling in alcohol use disorder and withdrawal: pathological involvement and therapeutic potential - Dharavath, Ravinder Naik; Pina-Leblanc, Celeste; Tang, Victor M.; Sloan, Matthew E.; Nikolova, Yuliya S.; Pangarov, Peter; Ruocco, Anthony C.; Shield, Kevin; Voineskos, Daphne; Blumberger, Daniel M.; Boileau, Isabelle; Bozinoff, Nikki; et al. (Frontiers in Neural Circuits, 2023)
Alcohol is one of the most widely used substances. Alcohol use accounts for 5.1% of the global disease burden, contributes substantially to societal and economic costs, and leads to approximately 3 million global deaths yearly. Alcohol use disorder (AUD) includes various drinking behavior patterns that lead to short-term or long-lasting effects on health. Ethanol, the main psychoactive molecule acting in alcoholic beverages, directly impacts the GABAergic system, contributing to GABAergic dysregulations that vary depending on the intensity and duration of alcohol consumption. A small number of interventions have been developed that target the GABAergic system, but there are promising future therapeutic avenues to explore. This review provides an overview of the impact of alcohol on the GABAergic system, the current interventions available for AUD that target the GABAergic system, and the novel interventions being explored that in the future could be included among first-line therapies for the treatment of AUD.